Islamic coping stress and quarter-life crisis among generation Z college students - Soraya, Siti Zazak; Puspitasari, Ratna Nila (Journal of Education and Learning (EduLearn), 2025)
The transition into adulthood often triggers anxiety and unease, colloquially known as the quarter-life crisis. During these challenging times, individuals frequently turn to Islamic stress-coping methods as a guiding light to navigate through this transformative phase of life. This research aimed to explore the relationship between Islamic stress coping and the quarter-life crisis among college students from generation Z. This study, conducted in a descriptive quantitative manner, involved the participation of 398 college students. Data was collected through a comprehensive questionnaire, and data analysis employed the product-moment correlation method. The study's findings revealed that, firstly, generation Z college students tend to exhibit a significantly high prevalence of Islamic stress coping; secondly, the level of quarter-life crisis experienced by these demographic leans towards a moderate, and most significantly, there is a positive correlation between Islamic coping stress and the quarter-life crisis experienced by generation Z college students. This correlation presents a moderately strong positive connection, underscoring the notion that the effective utilization of Islamic stress coping mechanisms positively influences the management and alleviation of the quarter-life crisis.